Degradation of tumour stromal hyaluronan by small extracellular vesicle-PH20 stimulates CD103+ dendritic cells and in combination with PD-L1 blockade boosts anti-tumour immunity. Issue 1 (1st December 2019) - Hong, Yeonsun; Kim, Yoon Kyoung; Kim, Gi Beom; Nam, Gi-Hoon; Kim, Seong A; Park, Yoon; Yang, Yoosoo; Kim, In-San
ABSTRACT: Highly accumulated hyaluronan (HA) not only provides a physiological barrier but also supports an immune-suppressive tumour microenvironment. High-molecular-weight (HMW)-HA inhibits the activation of immune cells and their access into tumour tissues, whereas, low-molecular-weight oligo-HA is known to potentially activate dendritic cells (DCs). In this paper, we investigated whether small extracellular vesicle (EVs)-PH20 hyaluronidase induces tumour HA degradation, which, in turn, activates DCs to promote anti-cancer immune responses. Informed by our previous work, we used a small EV carrying GPI-anchored PH20 hyaluronidase (Exo-PH20) that could deeply penetrate into tumour foci via HA degradation. We found that Exo-PH20-treatment successfully activates the maturation and migration of DCs in vivo, particularly CD103 + DCs leading to the activation of tumour-specific CD8 + T cells, which work together to inhibit tumour growth. Moreover, combination with anti-PD-L1 antibody provided potent tumour-specific CD8 + T cell immune responses as well as elicited prominent tumour growth inhibition both in syngenic and spontaneous breast cancer models, and this anti-tumour immunity was durable. Together, these results present new insights for HA degradation by Exo-PH20, providing a better understanding of oligo HA-triggered immune responses to cancer.